Effects of jump exercises with and without stretch-shortening cycle actions on components of physical fitness in prepubertal male soccer players - Bouguezzi, R.; Chaabene, H.; Negra, Y.; Moran, J.; Sammoud, S.; Ramirez-Campillo, R.; Granacher, U.; Hachana, Y. (Sport Sciences for Health, 2020)
Objective: This study examined the effects of 8-week stretch-shortening cycle-based (SSC-based) versus non-SSC-based jump exercises on physical fitness in prepubertal male soccer players. Methods: Twenty-six participants were randomly assigned to either a SSC-based using countermovement jump (CMJG; n = 13) or a non-SSC-based jump group using squat jump (SJG; n = 13). Pre- and post-training, tests were conducted to assess measures of muscle power (countermovement jump, reactive strength index), speed (5 m, 20 m), change of direction (CoD), and sport-specific performance (maximal kicking distance). To establish the effect of the interventions on the dependent variables, a 2 (group: CMJG and SJG) × 2 (time: pre, post) ANOVA with repeated measures was determined for each parameter. Results: Findings demonstrated a main effect of time for countermovement jump, reactive strength index, and maximal kicking distance (p < 0.05, effect size [ES] = 0.56-0.71). Group × time interactions were identified for (5 m, 20 m, and reactive strength index (p < 0.05, ES = 0.59-0.64) in favor of CMJG. Particularly, pre-post-performance improvements have been observed for 5 m ( d1.6%; p = 0.04; ES = 0.54) and 20 m (d 5.3%; p < 0.01; ES = 1.00) in the CMJG. For SJG, 5 m (d - 5.5%; p = 0.01; ES = - 1.12) and 20 m (d - 3.7%; p = 0.01; ES = - 0.82) pre-post-performance declines were observed. Regarding reactive strength index, pre-post-improvement was noted for CMJG only (d - 40.1%; p < 0.01; ES = 3.7). In addition, a tendency towards a group × time interaction was found for CoD (p = 0.06, ES = 0.54) with a performance decrement for SJG ( d- 6.0%; p < 0.01; ES = - 1.8) and no pre-post changes for CMJG (d 0.15%; p > 0.05; ES = 0.05). Conclusion: Overall, jump exercises which utilize the SSC seem to be more effective in improving measures of speed and muscle power performance in young athletes. However, jump exercises that do not involve the SSC appear to negatively affect CoD performance in young athletes.